Anomalous origin of the circumflex artery and patent foramen ovale: a rare cause of myocardial ischaemia after percutaneous closure of the defect. Issue 8 (14th July 2003) - Casolo, G; Gensini, G F; Santoro, G; Rega, L
Abstract : A 35 year old man with a history of transient ischaemic attack and atrial septal aneurysm underwent percutaneous closure of a patent foramen ovale (PFO) with a transcatheter device. After the procedure the patient developed effort angina not present previously. Transoesophageal echocardiography confirmed the absence of residual shunt but showed an abnormal linear image running behind the aortic root. Magnetic resonance imaging detected an anomalous origin of the circumflex coronary artery from the right coronary sinus. The anomalous artery was located between the aortic root and the PFO closing device, causing coronary insufficiency. This report describes a rare complication of transcatheter PFO closure.